Characterization of the subcellular organization of UBE3A in central nervous system neurons - Paiva, Bruna Sofia Fonseca (2023)
Angelman syndrome is a rare disease resulting from imprinting of the paternal allele and a mutation in the maternal allele at the level of the UBE3A gene. This syndrome results in reduced levels of expression of the Ube3a protein in several brain regions, including the hippocampus and cortex. Symptoms lie in motor difficulties, mental retardation and absence of speech. UBE3A is an E3 ligase, responsible for the ubiquitination of proteins, leading to proteasomal degradation. It has also been associated with changes in synaptic plasticity. Although several substrates of this protein have been identified with an important postsynaptic role, its role at the presynaptic level and the correlation with the symptoms encountered are still unclear. In this work, we performed a characterization of the expression of this protein in axons and growth cones of embryonic hippocampal neurons of rats and mice, and it was observed that UBE3A is expressed in distal axons, but also at the level of growth cones. We also observed that UBE3A colocalizes with presynaptic proteins. These results suggest that UBE3A is associated with the formation of CNS synapses in neuronal cells since its relationship with presynaptic proteins was detected in Glutamatergic and GABAergic neurons. Collectively, these data provide new insights into UBE3A function and may explain the cognitive alterations found in patients with Angelman Syndrome.